People from my neighbourhood - Kawakami, Hiromi, 1958-; Goossen, Ted (London : Granta Books, 2020)
"Take a story and shrink it. Make it tiny, so small it can fit in the palm of your hand. Carry the story with you everywhere, let it sit with you while you eat, let it watch you while you sleep. Keep it safe, you never know when you might need it. In Kawakami's super short 'palm of the hand' stories the world is never quite as it should be: a small child lives under a sheet near his neighbour's house for thirty years; an apartment block leaves its visitors with strange afflictions, from fast-growing beards to an ability to channel the voices of the dead; an old man has two shadows, one docile, the other rebellious; two girls named Yoko are locked in a bitter rivalry to the death. Small but great, you'll find great delight spending time with the people in this neighbourhood."--Provided by publisher.
Keywords: Neighbors -- Fiction